A Novel Bedside Diagnostic Technique for Acquired Tracheoesophageal Fistula - Rajendram, Nesha; Sobani, Muhammad Ariff; Mansor, Masaany; Kamarudin, Intan Kartika; Rahim, Norazila Abdul (International Journal of Human and Health Sciences (IJHHS), 2023)
Acquired tracheoesophageal fistula is a rare and challenging medical dilemma. In general, tracheoesophageal fistula (TOF) is diagnosed by subjecting a patient to imaging such as barium swallow or computed tomography of the neck and thorax. The patient may need a diagnostic bronchoscopy under general anaesthesia and flexible oesophagoscopy. We report three cases of suspected TOF diagnosed utilising a new, novel, minimally invasive, an office-based procedure in a bedside setting. TOF is difficult to diagnose. Our technique is practical, utilizes instruments in the clinic itself, is comfortable for the patient, and is inexpensive. The cases include a post tracheostomised patient who was suspected to be complicated with TOF, a patient who underwent OGDS for investigation of dysphagia and odynophagia with an incidental finding of oesophageal fistula, and a patient who underwent anterior cervical corpectomy and fusion with an open tracheostomy, who was suspected to have an oesophageal fistula post neck surgery. The technique used a flexible nasopharyngolaryngoscope (FNPLS), and a nasogastric tube instilled with methylene blue and local anaesthesia into the larynx and trachea in an awake patient. The detailed step-by-step procedure was described. This technique is simple and safe. It eliminates the need to subject patients to general anaesthesia or contrasted imaging in diagnosing TOF. International Journal of Human and Health Sciences Supplementary Issue: 2023 Page: S29